2012
DOI: 10.1590/s0100-29452012000300028
|View full text |Cite
|
Sign up to set email alerts
|

Características morfofisiológicas de plantas clonais de Passiflora alata crescidas em diferentes doses de nitrogênio e níveis de sombreamento

Abstract: Plantas clonais de Passiflora alata foram submetidas a quatro níveis de sombreamento (0; 25; 50 e 75%) aos 75 dias após o estaqueamento (DAE). Dez dias após, aplicou-se nitrogênio (N) nas dosagens de 0; 25;50; 100 e 200 mg N kg-1 de solo. Verificou-se, aos 175 DAE, interação significativa (p<0,05) entre níveis de sombreamento (NS) e doses de N, para todos os parâmetros fotossintéticos avaliados. Observou-se um aumento na taxa fotossintética líquida com a elevação de NS e de N até a dose de 146 mg N kg-1. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
2
2
0
4
Order By: Relevance
“…The increase in SLA indirectly resulted in a reduction of the leaf tissues. This pattern is corroborated by Freitas et al (2012), who observed a reduction in leaf tissues caused by nitrogen. Regarding excess salts, Munns and Tester (2008) reported that salt stress induces adjustments in leaf morphology, chlorophyll content, and biochemical processes.…”
Section: Morphophysiological Indicessupporting
confidence: 70%
See 1 more Smart Citation
“…The increase in SLA indirectly resulted in a reduction of the leaf tissues. This pattern is corroborated by Freitas et al (2012), who observed a reduction in leaf tissues caused by nitrogen. Regarding excess salts, Munns and Tester (2008) reported that salt stress induces adjustments in leaf morphology, chlorophyll content, and biochemical processes.…”
Section: Morphophysiological Indicessupporting
confidence: 70%
“…Nitrogen stimulates the production of leaf biomass and leaf area as well as the photosynthetic rate in passion fruit plants (FREITAS et al, 2012), thus exerting a positive effect on their growth and on the quality of their seedlings. Aref and Shetta (2013) observed that the application of ammonium sulfate or calcium nitrate not only favored the growth of seedlings of Ziziphus spina-christi (L.) Willd.…”
Section: Growth and Leaf Productionmentioning
confidence: 99%
“…This trend was also observed in Passiflora alata seedlings that obtained maximum photosynthetic values at low N doses (up to 146 mg kg −1 ) 176 d after staking [16]. It has been reported that tree plants exhibit increased N demand with increasing age and during fruit production [17], and two main sources of N that fruit trees use for their vegetative growth and reproduction are root N uptake and internal N cycling.…”
Section: Nitrogen Fertilization Increased Photosynthetic Rates Of Eugsupporting
confidence: 61%
“…The photosynthetic rate (A) increased up to a dose of 104.3% with a value of 15.51 µmol CO 2 m -2 s -1 ( Figure 2B). This result can be attributed to the fact that fertilization with these nutrients favors biosynthesis of photosynthetic components, such as the rubisco enzyme and chlorophyll molecules, inducing stomatal opening due to the greater demand for CO 2 (Freitas, Almeida, Lago, Souza, & Souza, 2012).…”
Section: Resultsmentioning
confidence: 99%